Properties of a Generalized Class of Weights Satisfying Reverse Hölder’s Inequality - S. H. Saker; S. S. Rabie; R. P. Agarwal (Journal of Function Spaces)
In this paper, we will prove some fundamental properties of the discrete power mean operator Mpun=1/n∑k=1n upk1/p,for n∈I⊆ℤ+, of order p, where u is a nonnegative discrete weight defined on I⊆ℤ+ the set of the nonnegative integers. We also establish some lower and upper bounds of the composition of different operators with different powers. Next, we will study the structure of the generalized discrete class BpqB of weights that satisfy the reverse Hölder inequality Mqu≤BMpu, for positive real numbers p, q, and B such that 0<p<q and B>1. For applications, we will prove some self-improving properties of weights from BpqB and derive the self improving properties of the discrete Gehring weights as a special case. The paper ends by a conjecture with an illustrative sharp example.